Pengaruh Metode Diskusi Langsung (Sharing) terhadap Minat Belajar Siswa pada Pelajaran Akidah Akhlak Kelas VIII di MTs NW Montong Mas - Muhammad Irwan Mansyuriadi; Firad Wijaya; Andri Afriani (Al-Munawwarah : Jurnal Pendidikan Islam, 2023)
Currently, teachers' teaching methods, strategies and techniques greatly influence students' interest and learning success in class. Therefore, it is necessary to develop the learning system by teachers. The application of learning strategies to increase students' interest in learning Islamic Religious Education at Madrasah Tsanawiah (MTs) NW Montong Mas as a basis for spiritual development towards the welfare of social life absolutely must be increased because the assumption is that religious education includes Aqidah Akhlak, Qur'an Hadith, Fiqh, If Arabic is used as a basis for developing spiritual values, if spoken well, social life will feel harmonious. Based on the results of observations, it shows that the weakness in learning Aqidah Akhlak lies in the lack of variety in learning, for example the use of methods that are repeated and have a lot of stories and make them bored or bored which results in students' lack of interest in learning and makes students passive or inactive in the process. learning Moral Creeds. This research aims to determine whether or not there is an influence of the direct discussion (Sharing) method on students' interest in learning in Class VIII Aqidah Akhlak lessons at MTs NW Montong Mas. In this research the author used quantitative methods, with an experimental design. Data collection uses questionnaires, observation, interviews and documentation, statistical data analysis, with the aim of testing predetermined hypotheses. The results of the post-test analysis of the t test obtained sig. 0.000 < 0.05 and it is known that t count > t table. From these two results it can be stated that there is an influence from the use of the direct discussion (Sharing) method on students' interest in learning in the Class VIII Aqidah Morals lesson at MTs NW Montong Mas in the academic year.